Only those who attempt the absurd will reach the impossible. High-flow nasal cannula oxygen therapy alone during weaning after extubation in a patient with tuberous sclerosis complex and lymphangioleiomyomatosis - Lanza, Maurizia; Imitazione, Pasquale; Musella, Salvatore; Annunziata, Anna; Fiorentino, Giuseppe (Anestezjologia Intensywna Terapia, 2020)
Dear Editor, The tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder. Pulmonary lymphangioleiomyomatosis (LAM) occurs in up to 40% of TSC patients and predominantly affects women. Most patients with TSC suffer from epilepsy, and many have cognitive and behavioral problems such as severe intellectual disability, autism, and hyperactivity. We report a case of a young woman who was intubated following convulsive status epilepticus which occurred in a state of clinical stability and who was weaned from orotracheal intubation exclusively using a high-flow nasal cannula (HFNC) with 1.0 FiO2. HFNC provides heated and humidified air with flow rates up to 60 L min-1 with relatively stable oxygen content (adjustable FiO2 0.21–1.0). In this case non-invasive ventilation (NIV) was not used due to the high risk of barotrauma caused by the progression of the cystic lung disease. HFNC proved effective to reduce inspiratory effort, enhance tidal volume by delivering high-flow oxygen and facilitate weaning from ventilators in this patient.